Penegakan Hukum Terhadap Pelanggaran Hak Cipta Atas Penggunaan/Menjual Karya Seni Penggemar (Fan Art) Orang Lain Tanpa Izin Di Internet - B, Erlina; Seftiniara, Intan Nurina; Sukma, Masayu Nirmala (Universitas Sang Bumi Ruwa Jurai, 2024)
Many people use fan art to use it as merchandise such as key chains, clothes, photo cards, accessories, including distributing their work without the permission of the fan art creator. The problem in this research is what are the factors that cause copyright infringement for using/selling other people's fan art without permission on the internet and how to enforce the law against copyright infringement for using/selling fan art? other people without permission on the internet. This research approach is normative juridical such as literature studies and empirical juridical such as data from the Directorate General of Intellectual Property Rights, Ministry of Law and Human Rights, Lampung Regional Office. Data analysis was carried out qualitatively. The research results show that the factors that cause copyright infringement are, first, lack of public knowledge and understanding of copyright protection. Second, to seek personal profit for commercial purposes. Third, the law enforcement aspect is still weak, because the creator did not take the matter to legal action. Law enforcement for copyright infringement has been regulated, but because of the offense of complaints, as long as the creator does not make a complaint, copyright disputes cannot be processed through criminal acts